A review of recent advances in exosomes and allergic rhinitis - Zheng, Zhong; Yu, Yangyang (Frontiers in Pharmacology, 2022)
Allergic rhinitis is a chronic inflammatory disease of nasal mucosa caused by the presence of IgE after exposure to allergens, characterized by nasal irritation, hypersecretion of the nasal passages and sneezing, which frequently occurs in children and adolescents. There has been an increase in allergic rhinitis over the past few years due to air pollution. Exosomes have been discovered to be nano-sized vesicles, which contain a wide range of substances, including proteins and nucleic acids, numerous studies indicates that exosomes play a vital role in cells communication. Recently there have been more and more studies exploring the role of exosomes in allergic rhinitis. Therefore, here we will present a comprehensive review of the research on exosomes and their role in allergic rhinitis for the purpose of providing new understanding of potential value of exosomes applied to the treatment of allergic rhinitis.